MULTIFACTOR ANALYSIS OF THE ONCOPROTEINS EXPRESSION DEPENDENCE IN GASTRIC CANCER - Kirkilevskiy, S.I.; Sulaieva, O.N.; Mashukov, A.A.; Rybin, A.I.; Bilenko, O.A.; Maksimovskiy, V.E.; Raciborskiy, D.V. (World of Medicine and Biology, 2020)
The total of 26 patients operated on for gastric cancer in the period of 2007-2011 was included in the study performed on the basis of the Abdominal Oncology Surgery Department at the CHPI “Odessa Regional Oncologic Dispensary”. In all cases, the so-called lymph node dissections were carried out based on principle considerations, i.e. extensive prophylactic biopsies of visually unchanged lymph nodes. A multifactor analysis of p53, VEGFR-3, Her2/new oncoproteins expression and Ki67 proliferative tumor activity dependence on the involvement of the tumor microcirculatory bed (ly, v), local growth (T), the presence of residual tumor tissue (R), the degree of tumor differentiation (G), the degree of regional lymph nodes involvement (N), the microinfiltration type (Inf α, β, Inf) was performed.
Keywords: gastric cancer; immunohistochemistry; oncoproteins